2022
DOI: 10.1183/23120541.00708-2021
|View full text |Cite
|
Sign up to set email alerts
|

An international survey on nasal nitric oxide measurement practices for the diagnosis of primary ciliary dyskinesia

Abstract: Nasal nitric oxide (nNO) measurements are routinely used in the assessment of patients suspected to have primary ciliary dyskinesia (PCD), but recommendations for performing such measurements have not focused on children and do not include all current practices. To guide the development of a European Respiratory Society-supported technical standard for nNO measurements in children, an international online survey was conducted to better understand current practices for measuring nNO among providers involved in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Ideally, nNO should be measured in a clinic or hospital space that has low ambient NO levels to avoid potentially artefactual results [30,31], but a recent survey showed that not all users measure ambient levels [20]. Environmental NO levels <20 ppb are generally considered acceptable to allow testing to proceed.…”
Section: Considerations For Consumablesmentioning
confidence: 99%
See 3 more Smart Citations
“…Ideally, nNO should be measured in a clinic or hospital space that has low ambient NO levels to avoid potentially artefactual results [30,31], but a recent survey showed that not all users measure ambient levels [20]. Environmental NO levels <20 ppb are generally considered acceptable to allow testing to proceed.…”
Section: Considerations For Consumablesmentioning
confidence: 99%
“…While children requiring PCD diagnostic testing typically have chronic upper and lower airway symptoms, these data strongly indicate that nNO measurements should not be measured during infective exacerbations. Many centres delay testing for 2-4 weeks following infection [20], but there is no evidence concerning the appropriate duration. In the absence of clear evidence, we suggest testing should be delayed 2-4 weeks after exacerbation symptoms have resolved and if doubt exists concerning a low nNO measurement the test should be repeated on a separate day.…”
Section: Training Of Personnelmentioning
confidence: 99%
See 2 more Smart Citations
“…<1 ppb with 1% linearity from 0.1 to 5000 ppb for CLD 88 (Eco Medics, Duernten, Switzerland)) than for widely used electrochemical devices ( e.g. ±5 ppb for values <50 ppb and 10% for values >50 ppb for Niox Vero (Circassia, Oxford, UK)) [ 2 ], little is known on the biological variability of nNO measurements, except for increased nNO output variability in adults with rhinitis compared with healthy subjects and the positive effect of training on the level of nNO taken during expiration against a resistance (nNO-ER) in children [ 3 , 4 ]. The PCD Foundation Clinical Center Network and Genetic Disorders of Mucociliary Clearance Consortium recommend sampling both nostrils for nNO-ER and to perform at least two measurements per nostril with the aim of obtaining a 10% repeatability [ 4 ].…”
mentioning
confidence: 99%